Pengaruh Kualitas Layanan Inti dan Kualitas Layanan Encounter terhadap Niat Beralih: Sebuah Peran Mediasi Kepuasan Pelanggan (Studi pada pengunjung Hotel Fitra dan Hotel Garden Majalengka) - Alan Rusdiana; L Suparto (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2022)
This research is a development of previous research. In this study, customer satisfaction is divided into two, namely transaction-based satisfaction and overall satisfaction. This type of research is associative research. This research takes the title: "The Influence of Core Service Quality and Encounter Service Quality on Switch Intention: A Mediation Role of Customer Satisfaction (Study on visitors to Hotel Fitra and Hotel Garden Majalengka)". The purpose of this study was to determine the partial effect of core service quality and encounters on switching intentions with mediating factors of customer satisfaction (transaction-based satisfaction and transaction-based satisfaction). The population in this study were all visitors to the Fitra hotel and the Garden Majalengka hotel. The number of respondents in this study amounted to 315 people who were taken using the sampling technique used was purposive sampling. The data analysis technique uses structural equation modeling (SEM) with the help of AMOS 21 software. The results of this study indicate that 1) the quality of the encounter service has a negative effect on the intention to switch, 2) the quality of the core service has no effect on the intention to switch, 3) the quality of the encounter service has a positive effect on transaction-based satisfaction, 4) the quality of the encounter service has a positive effect on overall satisfaction, 5) core service quality has a positive effect on overall satisfaction, 6) transaction-based satisfaction has a negative effect on switching intentions, 7) overall satisfaction has a negative effect on switching intentions, 8) transaction-based satisfaction mediates the negative effect of encounter service quality on switching intentions, 9) satisfaction overall mediates the negative effect of service quality encounter on core service switching intentions positively affects customer satisfaction, and 10) overall satisfaction mediates the negative effect of core service quality on switching intentions.